Common Ways to See Differently: Race, Mestizaje, and Criollismo as Seen by Blind People in Chile and Venezuela - Luis Angosto-Ferrández (Latin American Research Review)
This article explores understandings of race, mestizaje, and criollismo among blind people in Chile and Venezuela. It demonstrates that visually perceived markers are not self-evidently constitutive of race as a social category. Participants show sound knowledge of racialized categories but also reveal significant differences in the identification of racial markers and in the way that race informs their understandings of mestizaje and criollismo in Chile and Venezuela. In Chile, where racial markers convey identity fixity and intersect overtly with social class categorizations, mestizaje and criollismo are conceptualized as separate elements of national identity. In Venezuela, where racial markers convey more identity porosity, mestizaje and criollismo are conceptualized as intertwined foundations of national identity. These social configurations counter naturalizing conceptualizations of race and enable a reconsideration of how different notions of admixture continue to permeate ideals of personhood and social relations in Latin American countries. They also erode academic conceptualizations of race that unwittingly contribute to legitimize the naturalization of race in public discourse—and potentially in governmental policy and practice.